Time domain adaptation of left ventricular diastolic intraventricular pressure in elite female ice hockey athletes - Yang, Ping; Zhang, Jianmei; Xue, Jun; Bai, Yunfei; Yang, Hui; Zhang, Ruiping; He, Benxiang (Frontiers in Cardiovascular Medicine, 2023)
Background Ice hockey is a high-intensity dynamic sport for which competitive athletes train for longer than 20 hours each week for several years. The cumulative time of myocardial exposure to hemodynamic stress affects cardiac remodeling. However, the intracardiac pressure distribution of the elite ice hockey athletes' heart during adaptation to long-term training remains to be explored. This study aimed to compare the diastolic intraventricular pressure difference (IVPD) of the left ventricle (LV) between healthy volunteers and ice hockey athletes with different training times. Methods Fifty-three female ice hockey athletes (27 elite and 26 casual) and 24 healthy controls were included. The diastolic IVPD of the LV during diastole was measured by vector flow mapping. The peak amplitude of the IVPD during isovolumic relaxation (P0), diastolic rapid filling (P1), and atrial systole (P4); the difference in the peak amplitude between adjacent phases (DiffP01, DiffP14); the time interval between the peak amplitude of adjacent phases (P0P1, P1P4); and the maximum decrease rate in diastolic IVPD were calculated. Differences between groups, as well as correlations between hemodynamic parameters and training time, were analyzed. Results Structural parameters of the LV were significantly higher in elite athletes than in casual players and controls. No significant difference in the peak amplitude of the IVPD during the diastolic phase was found among the three groups. The analysis of covariance with heart rate as a covariate showed that P1P4 in the elite athlete and casual player groups was significantly longer than that in the healthy control group (p < 0.001 for all). An increased P1P4 was significantly associated with an increased training year (β = 4.90, p < 0.001). Conclusions The diastolic cardiac hemodynamics of the LV in elite female ice hockey athletes could be characterized by a prolonged diastolic IVPD, and P1P4 prolonged with an increase in the training years, reflecting a time–domain adaptation in diastolic hemodynamics after long-term training.